The role of urban planning in planning residential lands Case study of EL-Hasahisa city - Gezira state – Sudan2022 AD - Ismail, Dr.Abdulrazaq Hassen; Habibullah, Prof Tawadod Hussein (Thi Qar Arts Journal, 2024)
City planning leads to the improvement of the urban environment and the. The study aimed to identify the current state of urban planning for the city of EL-Hasahisa and to know the types of appropriate planning in the future., directed maps, and efforts made by the competent authorities, and identify the adequacy of public facilities in the city. The study adopted the historical, descriptive, analytical and statistical method. Information was collected by observation, interview and questionnaire. A random sample of (200) individuals representing (3%) of the study population was selected. The data was analyzed by Statistical Packages (SPSS). The study concluded that residential urban planning was affected by the geographical location and unplanned housing, in addition to the lack of space and the absence of a future plan. The intervention of the political authority in the executive work of planning affected the area and shape of the city and reduced the opportunities for planning in it, which led to the overlap and the transformation of the nearby farms into housing. And that the strip shape made the concentration of services in the center and affected their distribution, so it became not enough for the city. And the horizontal expansion as a result of the population increase, imposing urban extensions in any habitable location. The re-planning and upgrading of the old neighborhoods has a positive role in solving the problem of horizontal expansion and transforming it into vertical housing, as well as the expansion of the people outside the residential plans and the encroachment on the streets and opening them to facilitate access to services.